SOCIAL-PSYCHOLOGICAL THEORIES OF GENDER - Kozhedub, Olena; Sokolina, Olha; Levenets, Anna; Kulchytskyi, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . It is known that war determines transformational processes in society. The Russian-Ukrainian war was no exception. Already today we are observing how the social statuses and roles of men and women in the military organization and in society are changing. The military profession is no longer a purely male one. Many Ukrainian women perform tasks in the area of combat operations and, as a result, changes in gender identity are recorded. Scientific analysis of such transformations is still ahead. The purpose of this article is to analyze the socio-psychological concepts of gender, the understanding of which will allow the reader to understand its nature more deeply and will lay the foundation for rethinking the impact of the Russian-Ukrainian war on the gender identity of modern Ukrainians.M e t h o d s . The study used theoretical research methods – historical and logical methods of cognition.R e s u l t s . Separate provisions of psychological and social concepts of gender are analyzed within the framework of psychodynamic theory, social learning theory, cognitive development theory, "new gender theory", gender schema theory, gender lens theory, gender difference theory, social role theory, social expectation model and the concept of tokenism. It is established that the formation of a person's gender identity is a complex and multifaceted socio-psychological process (psychodynamic theory). It is found that the formation of a person's gender identity is determined by their belonging to biological sex; the authors indicate that gender differences are not innate, but are formed under the influence of such external factors as upbringing, training, reinforcement of the corresponding system of actions under norms and sanctions, etc. (social learning theory and cognitive development theory). It has been determined that the leading role in the formation of gender identity is played by social expectations, and the formation of a person's gender identity is accompanied by processes of segregation and convergence, which manifest themselves in various spheres of human life (the theory of the "new psychology of gender"). It has been found that androcentrism, gender polarization, and biological existentialism (the theory of the gender lens or the theory of the lens of culture) dominate in modern society.C o n c l u s i o n s . An analysis of known concepts of gender, which belong to various psychological and sociological theories, was carried out. Such an analysis allowed the authors to characterize the social and psychological nature of gender. In particular, the provisions of the psychodynamic theory, the theory of social learning, the theory of cognitive development, the "new theory of gender", the theory of the gender scheme, the theory of the gender lens, the theory of gender differences, as well as the concept of tokenism were considered. Understanding the essence of these theories will contribute to rethinking the specifics of the impact of the consequences of the Russian-Ukrainian war on the formation and development of the gender identity of modern Ukrainians.
Keywords: theory, concept, sex, gender, psychodynamic theory, social learning theory, cognitive development theory, "new gender theory", gender schema theory, gender lens theory, gender difference theory, token